Penerapan Model Project Based Learning untuk Meningkatkan Hasil Belajar Siswa Materi Kekayaan Suku Bangsaku Kelas III SD - Anshori, Moh Sholihul; Fardani, Much Arsyad; Sudjadi, Sudjadi (MASALIQ, 2025)
This study aims to improve the learning outcomes of third-grade students at SD 1 Kalirejo on the topic of My Ethnic Group’s Wealth through the implementation of the Project Based Learning (PJBL) model. This classroom action research was conducted over three cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 20 third-grade students in the second semester of the 2024/2025 academic year, comprising 10 male and 10 female students. The results show a progressive increase in learning mastery across each cycle, from 30% in the initial condition to 40% in the first cycle, 60% in the second cycle, and 80% in the third cycle. These outcomes demonstrate that the PJBL model is effective in enhancing students’ cognitive learning outcomes, as indicated by the achievement of the minimum mastery criterion of ≥75%. Moreover, project-based learning provides a more contextual and meaningful learning experience, encouraging active student engagement in the learning process. These findings confirm that the implementation of the PJBL model not only improves learning outcomes in the subject of Pancasila Education but also contributes to the development of 21st-century competencies at the elementary school level.